(untitled) (Práxis Educativa, 2025)
This article falls within research lines focused on: community integration, pedagogy, and assessment in teacher education and educational policies. It addresses the challenges of teaching in light of the tensions between mixophobia (fear and rejection of difference) and mixophilia (appreciation of plural coexistence/otherness), drawing on Zygmunt Bauman’s concepts and Paulo Freire’s pedagogy of hope. It presents hoping as an ethical and political commitment that goes beyond optimism, involving critical and resistant attitudes in a context shaped by global postmodernism. With an essayistic and narrative approach, the text invites readers to rethink teaching beyond the traditional boundaries of the classroom and formal curriculum, subverting normative and homogeneous practices. It explores, between the rejection of the other and the commitment to encounter, possible paths for humanizing educational practice. In this movement of boundary-crossing, fear and hope, rejection and welcome coexist. Thus, it proposes an educational practice committed to hope in oneself and in others, to the appreciation of difference, and to the construction of ethical-political relationships that promote healthy coexistence based on altruistic bonds. Keywords: Mixophilia. Mixophobia. Hope. Teaching. Education.